Ionics c - Wachsman, Eric.; Weppner, Werner; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Ionics is publishing original results in the fields of science and technology of ionic motion. This includes theoretical, experimental and practical work on electrolytes, electrode, ionic/electronic interfaces, ionic transport aspects of corrosion, galvanic cells, e.g. for thermodynamic and kinetic studies, batteries, fuel cells, sensors and electrochromics. Fast solid ionic conductors are presently providing new opportunities in view of several advantages, in addition to conventional liquid electrolytes. In addition to regular length papers, short communications ("Letters") are being published to allow rapid information of the scientific community about important findings, without need of extensive descriptions. Depending on the progress in various areas of Ionics, also summary reports and reviews will be considered for publication. Publishing: Original papers Short communications Reviews and progress reports.
Keywords: Renewable energy resources; Energy storage; Electrochemistry; Condensed matter; Optical materials; Electronic materials; Electrochemistry; Renewable and Green Energy; Optical and Electronic Materials; Condensed Matter Physics; Energy Storage